Contribution à l'approche de suivi du point de puissance maximale des système photovoltaïques pour des conditions uniform - هنيات, محمد الصالح; بن عون, الياس (Université d'El Oued, 2021)
"Summary In recent years, there has been considerable interest in renewable energies and more specifically photovoltaic energy. This project concerns the design and realization of the Buck-Boost type DC / DC converter in a photovoltaic chain controlled by technical INC-MPPT to ensure the pursuit of the maximum power supplied by a PV generator based on an Arduino UNO microcontroller. The effectiveness of the proposed controls is verified by experimental results. " "ملخص في السنىاث الأخيرة ، كان هناك اهتمام كبير بالطاقاث المتجددة وبشكل أكثر تحديدًا الطاقت الكهروضىئيت. يتعمق هذا المشروع بتصميم وانجاز محول DC / DC من نوع Buck-Boost في سمسمة كهروضوئية يتم التحكم فيها بواسطة تقنية INC-MPPT لضمان السعي لمحصول عمى أقصى طاقة يوفرها مولد PV عمى أساس متحكم Arduino UNO . يتم التحقق من فعالية الضوابط المقترحة من خلال النتائج التجريبية. "
RESEAUX ELECTRIQUESمذكرة ماستر تخصص
Keywords: Keywords: Photovoltaic, Buck-Boost converter, MPPT control.; الكممات المفتاحية: الطاقة الكهروضوئية ، محول Buck-Boost ، تحكم MPPT